Understanding the reasons for home delivery among forest based tribal women in Heggadadevana Kote taluk of Mysuru district in Karnataka, India - Prabhu, Manohar P.; Dutra, Alessandra C. A.; M. R., Seetharam (International Journal Of Community Medicine And Public Health, 2022)
Background: Skilled care during delivery is critical in preventing maternal deaths. Although India has taken many steps to alleviate the financial burden of institutional delivery, women of low socioeconomic status in marginalized, rural communities still have a higher rate of home deliveries than national average. This paper examines characteristics of women who deliver at home in tribal communities in Mysore, Karnataka State, India. Methods: The 69 women who had given birth at home between June 2013 and June 2017 were interviewed about their choice to deliver at home. Demographic data was compared to data obtained from all women who delivered in tribal communities in the same area and in the same time frame. Results: The findings from this study indicate that women who deliver at home have higher gravidity, have a greater number of living children and are older than the average. Additionally, most home deliveries occur in June and occur in the night time. Lastly, most women reported that their husbands decided on their delivery site. Conclusions: Data analysis and interviews reveal that increasing the number of institutional deliveries is a multifaceted issue that must take into account the demographic, economic and cultural factors behind the decision.